Does Perceptual Consciousness Overflow Cognitive Access? The Challenge from Probabilistic, Hierarchical Processes. (June 2017) - Gross, Steven; Flombaum, Jonathan
Abstract: Does perceptual consciousness require cognitive access? Ned Block argues that it does not. Central to his case are visual memory experiments that employ post‐stimulus cueing—in particular, Sperling's classic partial report studies, change‐detection work by Lamme and colleagues, and a recent paper by Bronfman and colleagues that exploits our perception of 'gist' properties. We argue contra Block that these experiments do not support his claim. Our reinterpretations differ from previous critics' in challenging as well a longstanding and common view of visual memory as involving declining capacity across a series of stores. We conclude by discussing the relation of probabilistic perceptual representations and phenomenal consciousness.